Pengaruh Makroekonomi terhadap Yield Spread Obligasi Indonesia Berdenominasi US Dollar - , Anil Kumar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Rapid and integrated developments and changes in the global financial environment has resulted the bond market to play an important role as an alternative source of funding in the current world economic environment, but not much is understood in the terms of macroeconomic factors that could influence the yield spread of the Indonesian US Dollar denominated bond. Researcher used a multifactor model to examines the impact of five macroeconomics factor namely: interest rate (BI Rate), Indonesia inflation rate (INFINDO), United states of America inflation rate (INFUS,) Indonesia credit default swap 10 years (CDS), and exchange rate fluctuation (USDIDR) on bond yield spread of the Indonesia Government Securities (IGS) and Corporate Bonds for a periode between February 2010 to May 2012. The findings support the expected hypotheses that CDS are the major drivers that influence the changes in short term maturity bond yield spreads and has no influence to the change in long term maturity bond yield spreads. However BI Rate, INFINDO, INFUS, and USDIDR have weak and no influence on both short term and long term maturity bond yield spreads respectively.